Pezoloma ciliifera (P. Karst.) Korf, un discomicete nuevo para España - Galán Márquez, Ricardo; García, Guy; Tena, R.; Ormad, Javier (Revista Catalana de Micologia, 2011)
Pezoloma ciliif era (p. Karst) Korf, a rare species in the world, is reported for the flIst tirne in Spain, on base to Albarracín mountains findings (Teruel, Spain). A detailed iconographic -macro and microscopicstudy is made. Besides, its ecological preferences are confrrmed, having a saprophytic habit in behaviour areas, during surnrner, at high elevations.